A tandem dearomatization/rearomatization strategy: enantioselective N-heterocyclic carbene-catalyzed α-arylation. Issue 8 (15th January 2019) - Wu, Zijun; Wang, Jian
Abstract : In this study, the first example of carbene-catalyzed tandem dearomatization/rearomatization reaction of azonaphthalenes with α-chloroaldehydes is described. Abstract : In this study, the first example of the carbene-catalyzed tandem dearomatization/rearomatization reaction of azonaphthalenes with α-chloroaldehydes is described. This protocol enables the efficient assembly of chiral dihydrocinnolinone derivatives in good yields with excellent enantioselectivities (up to 99% ee). Moreover, this strategy enables not only the highly enantioselective NHC-catalyzed nucleophilic aromatic substitution, but also a formal Csp 2 –Csp 3 bond formation.